Successful Therapeutic ERCP in a 99-Day-Old Child With Common Bile Duct Stones: A Case Report and Discussions on the Particularities of the ERCP in Children - Lou, Qifeng; Sun, Jianliang; Zhang, Xiaofeng; Shen, Hongzhang (Frontiers in Pediatrics, 2020)
Backgroud：At present, therapeutic endoscopic retrograde cholangiopancreatography (ERCP) has gradually been used in the diagnosis and treatment of biliary and pancreatic diseases in children, but reports on and the application of ERCP in children, especially in infants, are still highly limited. Case Presentation：This case report describes a 99-day-old infant with choledocholithiasis who successfully underwent ERCP to relieve an obstruction. The infant developed obstructive jaundice during chemotherapy for a malignant tumor, and a routine blood examination showed signs of infection. Liver damage also occurred. B-ultrasound suggested stones in the lower segment of the common bile duct（CBD）. After sufficient communication and preparation, biliary drainage was successfully carried out in the infant using adult duodenoscope (JF240) and related instruments with cooperation from the Department of Anesthesiology. Conclusions：This paper preliminarily introduces our experience with adult duodenoscope in children, providing a good example for hospitals without a special duodenoscope for children to carry out pediatric ERCP. Clinicians should pay close attention to the need of careful use of ERCP in infants.